2017
DOI: 10.1007/s10549-017-4527-7
|View full text |Cite
|
Sign up to set email alerts
|

The importance of early detection of calcifications associated with breast cancer in screening

Abstract: Purpose The aim of this study was to assess how often women with undetected calcifications in prior screening mammograms are subsequently diagnosed with invasive cancer. Methods From a screening cohort of 63,895 women, exams were collected from 59,690 women without any abnormalities, 744 women with a screen-detected cancer and a prior negative exam, 781 women with a false positive exam based on calcifications, and 413 women with an interval cancer. A radiologist identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…[7a] Detecting and monitoring increased calcification can be av aluable early indication of breast cancer. [8] Conversely,m onitoring the decrease in mineralization can be usefulf or assessing osteoporosis. [9] In addition, evidencei s emerging that HAP deposition mayp lay ar ole in the development and progression of age-related maculard egeneration in the retina and neurodegenerationi nt he brain.…”
mentioning
confidence: 99%
“…[7a] Detecting and monitoring increased calcification can be av aluable early indication of breast cancer. [8] Conversely,m onitoring the decrease in mineralization can be usefulf or assessing osteoporosis. [9] In addition, evidencei s emerging that HAP deposition mayp lay ar ole in the development and progression of age-related maculard egeneration in the retina and neurodegenerationi nt he brain.…”
mentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ of breast cancer calcification via mammography as part of breast cancer diagnoses 9,10 . However, Kojima and collegues reported that abnormal breast calcifications were only detected in 22% of TN-DCIS compared to 59-72% of other types of DCIS cases, emphazising the challenge associated with detecting this specific breast cancer subtype during its non-invasive term 7 .…”
mentioning
confidence: 99%
“…De acuerdo con lo estipulado con el PDSP existe una proporción de los casos de mortalidad, morbilidad y discapacidad que pueden clasificarse como evitables teniendo en cuenta la existencia de los servicios de salud y la tecnología necesaria, de modo que su presencia significa fallas en el proceso de atención. La gran mayoría de cánceres no palpables detectados a partir de calcificaciones son DCIS, de los cuales menos del 20 % son de bajo grado, considerados generalmente como sobrediagnóstico, ya que no impacta la reducción de la mortalidad de los pacientes que lo sufren (Mordang et al, 2018). Sin embargo, en una mamografía categorizada como BI-RADS 3 no es posible para un radiólogo distinguir entre calcificaciones asociadas a un DCIS de bajo grado y formas más agresivas del mismo (grado II o III), que deberían ser detectadas lo más pronto posible (Bijker et al,…”
Section: Justificaciónunclassified